OUR STUDY WAS AN ANALYSIS OF POSSIBLE ALLERGENS THAT CAUSE ACD IN CHILDREN AT THE AGE - Jalilov Asliddin Xolmatovich; Achilova Feruza Axtamovna (PEDAGOGS, 2024)
Abstract: The task set before us to write this article was Our study was an analysis of possible allergens that caused ACD in children aged 5 to 17 years. To achieve our goals and objectives, we analyzed the analysis of outpatient records of 26 children with ACD who applied in 2015-2017. There were 15 girls (57.7%), 11 boys (42.3%). 5 (19.2%) children suffered from atopic dermatitis, 2 (7.6%) - strophulus , 8 (30.1%) - food allergies. Some of the children with ACD who applied to the department had another referral diagnosis: perioral dermatitis - in 6 (23.0%), blepharitis - in 2 (7.6%), dyshidrosis - in 2 (7.6%). As a result, we came to the conclusion that Patch testing is the gold standard for diagnosing allergic contact dermatitis. The list of common allergens that cause allergic contact dermatitis in children can vary depending on many factors, such as the environment, and depending on the lifestyle the child leads and what objects he interacts with.